The Importance of Histopathological Examination to the Final Diagnosis of Peripheral Odontogenic Tumors: A Case Report of a Peripheral Odontoma - Marcio Augusto de Oliveira; Bruna Reis; Debora Pallos; Yeon Jung Kim; Paulo Henrique Braz-Silva; Fabiana Martins (Hindawi Limited, 2019)
A 30-year-old Caucasian man presented with an 18-month history of an asymptomatic calcified mass, located on the buccal side of the alveolar ridge. Medical records did not present any underlying conditions. On intraoral examination, the lesion was located on the right side of the maxilla, showing mucosal fenestration with mineralized tissue measuring approximately 1 cm in diameter. Radiographic examination showed multiple radiopaque masses. Incisional biopsy was performed, and histological analysis revealed a presence of enamel matrix, dentin, and cementum, resembling tooth-like structures. Surgical removal was offered after the diagnostic confirmation of peripheral odontoma, but the patient refused because of the asymptomatic nature of the lesion.